INTERPROFESSIONAL COLLABORATION AND TEAMWORK PRACTICES IN POST-OPERATIVE WOUND CARE MANAGEMENT AT HOSPITAL OF BANDA ACEH - Isneini Isneini; Hermansyah Hermansyah; Nurleli Nurleli; Erlangga Galih Zulva Nugroho; Fida' Husain (P3M Universitas 'Aisyiyah Surakarta, 2023)
The practice of surgical wound care requires teamwork of wound nurses and interprofessional collaboration in developing quality wound care procedures. The purpose of this study was to determine the relationship between interprofessional collaboration practices and nurse teamwork on the quality of wound care management in postoperative patients at RSUD Dr. Zainoel Abidin Banda Aceh (RSUDZA) in 2022. This research is a quantitative study with a correlative approach by making cross-sectional observations with a sample size of 52 nurses in 6 inpatient rooms at the Regional General Hospital dr. Zainoel Abidin (RSUDZA) Banda Aceh. Data collection was carried out by distributing questionnaires to respondents. The practice of interprofessional collaboration and team work of nurses in RSUDZA are mostly in the fairly good category and most are in the moderate level. However, there was a significant relationship between Interprofessional collaborative practice and the quality of postoperative wound care management (p = 0.0001) and there was a significant relationship between Team Nurse Practice and the quality of postoperative wound care management (p = 0.014). The conclusion of the study was that there was a relationship between the medical team's interprofessional collaborative practice and the nurse's teamwork practice with the quality of postoperative wound care management in the postoperative inpatient ward of RSU dr. Zainoel Abidin Banda Aceh. it is suggested that there is an increase in collaboration practices, teamwork and better management of surgical wound care in the service.